2017
DOI: 10.1038/s41598-017-16418-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial alterations in salivary microbiota and their association in oral cancer

Abstract: Oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of the oral cavity and the fourth leading malignancy and cause of cancer-related death in the male population of Taiwan. Most cases are detected at advanced stages, resulting in poor prognosis. Therefore, improved detection of early oral health disorders is indispensable. The involvement of oral bacteria in inflammation and their association with OSCC progression provide a feasible target for diagnosis. Due to the nature of oral neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
175
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(194 citation statements)
references
References 48 publications
4
175
0
3
Order By: Relevance
“…Fusicatenibacter was the most abundant genus that was underrepresented in patients with cancer, whereas the most abundant genera that were overrepresented in patients with cancer included Dorea , Ruminococcus , Dialister , Parabacteroides , Ruminoclostridium , and Alistipes . The overabundance of genera such as Dorea and Alistipes is consistent with prior studies that have compared the oral microbiome of patients with H&N cancer with that of control subjects . Taxonomical studies have suggested Alistipes species as a tumor‐promoting bacteria in colon cancer through increased IL‐6 signaling .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fusicatenibacter was the most abundant genus that was underrepresented in patients with cancer, whereas the most abundant genera that were overrepresented in patients with cancer included Dorea , Ruminococcus , Dialister , Parabacteroides , Ruminoclostridium , and Alistipes . The overabundance of genera such as Dorea and Alistipes is consistent with prior studies that have compared the oral microbiome of patients with H&N cancer with that of control subjects . Taxonomical studies have suggested Alistipes species as a tumor‐promoting bacteria in colon cancer through increased IL‐6 signaling .…”
Section: Discussionsupporting
confidence: 85%
“…Recently, small subunit ribosomal RNA (16S rRNA) studies have been used to identify oral bacterial taxonomic lineages and microbial differences between patients with cancer and normal subjects . Changes in the oral microbiome and their association with surgical resection also have been reported in oral cancer progression …”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐three non‐specific sequence‐based identification studies of the microbiota were included, 14 of which were published in 2017–2018 (Table ) (Al‐Hebshi, Nasher, Idris, & Chen, ; Al‐Hebshi et al., ; Bebek et al., ; Börnigen et al., ; Guerrero‐Preston et al., , ; Hayes et al., ; Hooper et al., ; Hu, Zhang, Hua, & Chen, ; Lee et al., ; Li et al., ; Mukherjee et al., ; Perera et al., , ; Pushalkar et al., , ; Schmidt et al., ; Shin et al., ; Wang et al., ; Wolf et al., ;Yang, Huang et al., ; Yang, Yeh et al., ; Zhao et al., ). Twenty‐one studies focused on bacterial identification (all by 16S rRNA gene regions), one of which also identified fungi (ITS2 gene fragment), one only fungi, and one was restricted to viral identification (human rRNA detection followed by search for viral sequences).…”
Section: Resultsmentioning
confidence: 99%
“…() reported that the total abundance of Streptococcus, Dialister and Veillonella discriminated patients with HNSCC from controls, and Lee et al. () found that the abundance of Bacillus, Enterococcus, Parvimonas, Peptostreptococcus and Slackia discriminated saliva samples of patients with OSCC from controls. At the species level, Yang, Yeh et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation